Classification of Music genres using Machine Learning (International Journal of Scientific Research and Management (IJSRM), 2022)
In today’s world, Music is a core part of human civilization, it is a form of expression that helps us in conveying our deepest emotions which we are unable to do in simple words. Not only as a form of expression but also a medium to find symphony, peace, and a sense of belongingness in oneself. Since we all usually enjoy different kinds of music genres as per our preferences, wouldn’t it be bliss if we had some kind of framework to categorize these melodies into different genres.